China's charm offensive and peacekeeping: the lessons of Cambodia – what now for Sudan? - Hirono, Miwa (Taylor & Francis, 2011)
China's participation in UN peacekeeping is often viewed as a part of a global ‘charm offensive’ aimed at enhancing China's image in host countries. However, when viewed in the light of its support for dictatorial regimes in those host countries, do Chinese peacekeeping efforts improve the perceptions local populations have of China? This article examines changes in Cambodian perceptions of China during the UN Transitional Authority in Cambodia (UNTAC) from 1992 to 1993. It argues that China's peacekeeping contribution to UNTAC helped to overcome negative perceptions of that country rooted in its support of the Khmer Rouge before 1992. The key to overcoming current negative perceptions is to project an image of Chinese neutrality with respect to all parties in a civil war. This article concludes by discussing the implication of this argument with regard to China's peacekeeping in Sudan from 2006 to the present, and suggesting that China will need to be more attentive to the needs of other warring factions in the north–south and Darfur conflicts.